Szapor, Judith, Hungarian Women’s Activism in the Wake of the First World War: From Rights to Revanche. London: Bloomsbury Academic, 2018. 207 pp. Illus. - Judit Acsády (Hungarian Cultural Studies, 2018)
Szapor, Judith, Hungarian Women’s Activism in the Wake of the First World War: From Rights to Revanche. London: Bloomsbury Academic, 2018. 207 pp. Illus.